Working with oral history: reflections on research procedures - Lang, Alice Beatriz da Silva Gordo (Cadernos CERU, 2000)
Spanish immigrants to Brazil have been doubly excluded first, because of their poverty and second because of the second class satatus of immigrants in general. For this reason, oral interviews give life to memories not usually preserved by records and archives. This research will analyse the testimony of six Andalusian women from the first wave of Spanish immigration, focusing on their style of life, the solidarity of compatrists, and questions of home, work and feeling of insecurity.